Numerical Magnitude Affects Accuracy but Not Precision of Temporal Judgments - Shukla, Anuj; Bapi, Raju S. (Frontiers in Human Neuroscience, 2021)
A Theory of Magnitude (ATOM) suggests that space, time, and quantities are processed through a generalized magnitude system. ATOM posits that task-irrelevant magnitudes interfere with the processing of task-relevant magnitudes as all the magnitudes are processed by a common system. Many behavioural and neuroimaging studies have found support in favour of a common magnitude processing system. However, it is largely unknown whether such cross-domain monotonic mapping arises from a change in accuracy of the magnitude judgments or results from changes in precision of the processing of magnitude. Therefore, in the present study, we examined whether large numerical magnitude affects temporal accuracy or temporal precision or both. In other words, whether numerical magnitudes change our temporal experience or simply bias our duration judgments. The temporal discrimination (between comparison and standard duration) paradigm was used to present numerical magnitudes (“1”, “5” and “9”) across varied durations. We estimated temporal accuracy (PSE) and precision (Weber ratio) for each numerical magnitude. The results revealed that temporal accuracy (PSE) for large (9) numerical magnitude was significantly lower than that of small (1) and identical (5) magnitudes. This implies that the temporal duration was overestimated for large (9) numerical magnitude compared to small (1) and identical (5) numerical magnitude, in line with ATOM’s prediction. However, no influence of numerical magnitude was observed on temporal precision (Weber ratio). The findings of the present study suggest that task-irrelevant numerical magnitude selectively affects the accuracy of processing of duration but not duration discrimination itself.